พฤติกรรมการแข็งตัวของโลหะผสมอะลูมิเนียม-ซิลิคอน ไฮเปอร์ยูเทกติกที่หล่ออย่างต่อเนื่อง - อนุรดี ทองธีรภาพ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Hypereutectic Al-Si alloys are attractive materials to many industries because they show interesting properties such as high strength and hardness and low thermal expansion coefficient. But coarse Si particles decrease ductility and cause initial crack. Solidification behaviour of continuously cast hypereutectic of Al-20 wt% Si alloys by using low-frequency electromagnetic vibration (LFEV) technique were studied. Diameter of ingot is 100 mm. The effects of low frequency of an alternate current and addition of chromium and/or iron were tested. The frequency lower than 37 Hz promoted inhomogeneous distribution of primary Si due to high turbulence in melt. In experiment, the optimum case of average diameter of primary Si with applied frequency at 27 Hz was about 19 µm. Cr addition, even on the strong magnetic stirring of 15 Hz, shows refinement (average diameter of primary Si was about 18 µm) and homogeneous distribution of primary Si, because of the formation of Si2Cr before Si crystallization makes the liquid more viscous therefore prevent the floating up of Si.